Indonesia - Budiasa, I Made; Adhiti, Ida Ayu Iran; Wirawan, Komang Indra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This study aims to determine the success of the drill and practice learning model in improving student achievement and learning response. The techniques and tools for obtaining data are the test method in the form of student work sheets, the observation method in the form of student response assessment format, and the questionnaire method in the form of written questions along with answer choices and data processed using descriptive statistical methods. Applying the drill and practice learning model succeeded in improving the ability to aksara wresastra and pangangge suara characters in class III A SD No. 3 Benoa 2018/2019 school year. This can be seen from the average value of the test results in the first cycle of 79.8 or 71.87% with sufficient predicate, and increased in the second cycle stage by 81.42 or 93.75% with a good predicate. In the response of students experiencing success it is evident from the average value of the first cycle of 78.32 or 71.87% with sufficient predicate, then increased in the second cycle of 86.71 or 93.75% with a good predicate.